Cutaneous silent period in masseter muscles: a clinical and electrodiagnostic evaluation. - Ongerboer de Visser, B W (1976)
In 35 normal subjects electromyographic silent periods were constantly evoked bilaterally in the masseter muscles during maximal contraction after unilateral electrical stimulation over the infraorbital or mental nerve. Findings in this study and data obtained in 30 patients suffering from trigeminal (26) and facial (four) nerve lesions suggest that the silent period evoked according to our methods is cutaneous in origin. The trigeminal sensory root forms the afferent limb of the silent period reflex. Its central pathway is thought to pass both crossed and uncrossed through the pons. Determination of the cutaneous silent period might be of value for the demonstration of trigeminal nerve lesions and to supplement results concerning other brain-stem reflexes.